2013
DOI: 10.4012/dmj.2013-129
|View full text |Cite
|
Sign up to set email alerts
|

Repair of silorane-based composites: Microtensile bond strength of silorane-based composites repaired with methacrylate-based composites

Abstract: The purpose of our study was to evaluate the effects of surface treatment on the microtensile bond strength (MTBS) of silorane-based composites (Filtek Silorane, 3M ESPE) repaired with methacrylate-based composites (Ceram X, Dentsply). The MTBS were measured before or after thermo-mechanical fatigue simulation (FS). The surface conditioning regimes were: no treatment, bonding agent, silane, and silane+bonding agent. Before and after FS, no significant differences could be observed among the different pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…There were no significant statistical differences in the bond strength of experimental groups in the study. It is consistent with previous studies (6,16,18,23,24,35). It was found that adhesive generation is not important for having a successful composite repair.…”
Section: Shapiro-wilk Test Was Used For Evaluating Data Distributionsupporting
confidence: 92%
“…There were no significant statistical differences in the bond strength of experimental groups in the study. It is consistent with previous studies (6,16,18,23,24,35). It was found that adhesive generation is not important for having a successful composite repair.…”
Section: Shapiro-wilk Test Was Used For Evaluating Data Distributionsupporting
confidence: 92%
“…SIL-based composite is more resistant to water sorption and disintegration, and this leads to smaller changes in material properties resulting from aging. [24,27] SIL-based composite could only be used effectively as a repair composite for aged SIL with the surface treatment combination of DB and OA. Although, the poor shear bond strength results along with the high rate of adhesive failures that the failure mode analysis showed for this group are evidence of the weakness of bonding in this context.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary a new research on microtensile bond strength of SIL-based composites repaired with MC-based composites showed that silane did not contributed to an increase in the tensile strength. [24] In this study, a silane solution was not employed prior to the adhesive, in order to focus on the influence of grinding and conditioning of the repair surface on the bond. Implementation of silane enhances the wetting of the surface for the bonding agent, which then infiltrates easily into the irregularities created by the surface roughening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite improvements in the properties of composite materials, phenomena such as fracture of the restoration, chipping and discoloration may occur, the dentist needing to repair or replace that obturation [3].…”
mentioning
confidence: 99%